Kedudukan Hukum Pemilih Non E-Ktp Dalam Pemilihan Umum Tahun 2019 Dan Tahun 2024 Di Provinsi Papua - Ahmad Rifai Rahawarin; Muslim Muslim; Farida Tuharea; Zonita Rumalean Zirhani Rumalean; Wahyudi BR; Desy Maryani (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2023)
The essence of the right to vote for Non-e-KTP Voters in the democratic system and Human Rights in the general election system in Papua Province consists of the essence of the right to vote Non-e-KTP from a democratic perspective in Papua, which is very different from the highest defeat in the hands of the people but based on law, so In Papua, the noken system applies, whose democracy is based on consensus deliberation with a delegation system represented by big people or a bond system without being questioned about the use of e-KTP, and a direct voting system by those who have the right to vote determined by e-KTP. As well as the essence of the right to vote for non-e-KTP voters from the perspective of human rights in Papua, namely the rights of citizens to vote as human rights and constitutional rights of citizens can be through the use of the right to vote directly by voters who have e-KTP to exercise their rights and can represented by a traditional leader who represents and on behalf of the community to determine elections. From the perspective of human rights and justice, theoretically it can be said that it fulfills a sense of cumulative justice, but individually it can be said that it does not fulfill a sense of justice.Esensi hak memilih Pemilih Non e-KTP pada sistem demokrasi dan Hak Asasi Manusia dalam sistem pemilihaan umum di Provinsi Papua terdiri dari esensi hak memilih pemilih Non e-KTP perspektif demokrasi di Papua yaitu sangat erat hubungannya dengan kedaulatan tertinggi berada ditangan rakyat namun berdasarkan hukum, sehingga di papua berlaku sisten noken yang demokrasinya berdasarkan musyawarah mufakat dengan sisten delegasi yang diwakili oleh big man atau sistem ikat tanpa dipermasalhakan penggunaan e-KTP, dan sistem pencoblosan lansung oleh yang memiliki hak memilih yang ditentukan oleh e-KTP.  Serta esensi hak memilih pemilih Non e-KTP perspektif Hak Asasi Manusia di Papua yaitu hak-hak warga negara untuk memilih sebagai hak asasi manusia dan hak konstitusional warga negara dapat memalui penggunaan hak memilih langsung oleh pemilih yang ber e-KTP untuk menggunakan haknya dan dapat diwaili oleh ketua adat yang mewakili dan atas nama masyarakat untuk menentukan dalam pemilu yang dilihat dari perspektik hak asasi manusia dan kedilan secara teoritik dapat dikatakan memenuhi rasa keadilan komulatif namun secara individu dapat dikatakan tidak memenuhi rasa keadilan.